PEMODELAN PRODUK DOMESTIK REGIONAL BRUTO (PDRB) PROVINSI JAWA TENGAH DENGAN PENDEKATAN SPASIAL AUTOREGRESSIVE MODEL PANEL DATA - Ulfatun Khasanah; Abdul Karim; Indah Manfaati Nur (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Modeling spatial is modeling that deals with approach point and area .While regression analysis data panel is regression analysis based on data panel toobserve the relation between one variable bound ( dependent variables ) withone or more variables free ( independent variables). Approach used is themodel spatial autoregressive (SAR). Model spatial autoregresive is a modelcombined model regression simple with lag spatial on the variables ofdependent using data cross section . The data used was data gdp and factorswhich influence it namely the local revenue, population, and investment 20112015year Based on Hausman test for the above model SAR is hisq = 0.50389, df = 3, p-value = 0.918. This means that p-value> 0.05 thus, the selected model is SARrandom effects.Keywords :PDRB, Spatial Panel, Spatial Autoregressive (SAR)